AL-QURAN DAN INTERPRETASI IDEOLOGIS - M. Taufiq Hidayat; Yusuf Rahman (LP2M Universitas PTIQ Jakarta, 2022)
This paper proves that the ideological construction of an interpretation will determine the tendency of a product of interpretation and has the potential to reduce the meaning of a text and even reject other interpretations. The product of such interpretation is only more concerned with the process of elaborating verses for certain interests by designing themes and sub-themes as well as tendentious conclusions and even blaming